EJERCICIO Nº 7

f ( x) = x + 1 ⋅ x + 1 = x + 1 · x + 1
2 2 2 2

(

)

(

) (

)

1 2

= x +1
2

(

)

3 2

f ' ( x) =

3 · x2 +1 2

(

)

3 −1 2

· ( 2x) =

NO PASES A LA SIGUIENTE HOJA HASTA QUE NO HALLAS ENTENDIDO ÉSTA. INTENTA ACABAR EL EJERCICIO ANTES DE VER LA SOLUCIÓN

EJERCICIO Nº 7

f ( x) = x + 1 ⋅ x + 1 = x + 1 · x + 1
2 2 2 2

(

)

(

) (

)

1 2

= x +1
2

(

)

3 2

3 −1 3 2 f ' ( x) = · ( x + 1) 2 · ( 2 x ) = 2 1 3 2 · ( x + 1) 2 · ( 2 x ) = 2

NO PASES A LA SIGUIENTE HOJA HASTA QUE NO HALLAS ENTENDIDO ÉSTA. INTENTA ACABAR EL EJERCICIO ANTES DE VER LA SOLUCIÓN

EJERCICIO Nº 7

f ( x) = x + 1 ⋅ x + 1 = x + 1 · x + 1
2 2 2 2

(

)

(

) (

)

1 2

= x +1
2

(

)

3 2

3 −1 3 2 f ' ( x) = · x + 1 2 · ( 2 x ) = 2 1 3 2 · x +1 2 · ( 2x) = 2

(

)

(

)

3x · x 2 + 1
SOLUCIÓN:

f ' ( x) = 3x · x 2 + 1